Transverse barrier formation by electrical triggering of a metal-to-insulator transition - Pavel Salev (Nature Portfolio, 2021)
Resistive switching usually occurs by the formation of conducting filaments in the direction of current flow. Here the authors study an intriguing type of volatile metal-to-insulator resistive switching in (La,Sr)MnO3, which occurs by the formation of an insulating barrier perpendicular to the current.